Aborigines and Tin Mining in North Queensland: A Case Study in the Anthropology of Contact History - Anderson, Christopher (The Australian journal of anthropology, 1983)
Much of the 'new history'of Aboriginal contact with Europeans in Australia lacks an adequate socio-cultural understanding of Aboriginal society and its diversity. Attempts to produce overall models of contact have obscured, too, the diversity of European activity and its impact. The outcome has been too hollow and passive a view of Aboriginal responses to Australian colonial situations. The aim of the present paper is to examine, from an anthropological perspective, a particular contact relationship: tin-mining and Kuku-Nyungkul Aborigines in southeast Cape York Peninsula, north Queensland, between 1885 and 1940. Iargue that it is only through such case studies that we can gain adequate insight into Aboriginal perspective' on colonial history.